Analysis of the Traditional Values Based on Syara', Syara' Based on Kitabullah for Skills-Based Innovation - Astalini, Astalini; Darmaji, Darmaji; Agus Kurniawan, Dwi; Yusnidar, Yusnidar; Harizon, Harizon; Salsabilla Nurma Yahya, Gita; Suryati, Sri (Indonesian Journal of Education Research (IJoER), 2024)
Purpose of the study: The aim of this research activity is to find out about the description of the customary syara', syara' based on Kitabullah, find out about the description of skills-based innovation, and find out the results of the value analysis of the customary syara', syara' based on Kitabullah for skills-based innovation at Al-Hidayah Methodology: The type of research used is quantitative research. This study uses data in the form of numbers as a tool to analyze the information to be known. The population used is teachers at the Al-Hidayah Foundation with a sample of 21 teachers. The instruments used are questionnaires and interviews, and the data analysis technique used is descriptive statistical testing. Main Findings: The results of the study obtained in the teacher response questionnaire showed that teachers who chose strongly agree had a percentage of 23.8%, in the agree category 66.6%, in the neutral category 9.5%, and 0% in the disagree and strongly disagree categories. The results of the study in the teacher perception questionnaire showed that the percentage was 14.2% in the strongly agree category, in the agree category 61.9%, then the neutral category 23.8%, then 0% in the disagree and strongly disagree categories. Novelty/Originality of this study: Customary values ​​based on Islamic law and the book of Allah can be applied in learning, such as in the curriculum and non-academic activities, namely cultural extracurricular activities such as dance and tradiitional music. The use of these customary values ​​is not only beneficial for students, but also for schools that implement them because they can advance the school environment.